An Efficient Palladium-Catalyzed α-Arylation of Acetone Below its Boiling Point - Richardson, Jeffery; Mutton, Simon P.; Martin, Fionna M.; Walton, Lesley; Ledgard, Andrew J. (Synlett, 2020)
The monoarylation of acetone is a powerful transformation, but is typically performed at temperatures significantly in excess of its boiling point. Conditions described for performing the reaction at ambient temperatures led to significant dehalogenation when applied to a complex aryl halide. We describe our attempts to overcome both issues in the context of our drug-discovery program.
Keywords: arylation; cross-coupling; drugs; ketones; medicinal chemistry; palladium